Peranan Pimpinan dalam Pengembangan Lembaga Pendidikan Islam - Khoirul Anam (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Education is important in preparing and improving the quality of human resource in Indonesia. A well developed education system implies on the high quality of Islamic education in empowering Muslims in Indonesia to face globalization and reformation era. For private Islamic education, the role of the committee is central to make the institution excellent and outstanding.